Does the Feminisation of Agricultural Labour Empower Women? Insights from Female Labour Contractors and Workers in Northwest Syria. (21st May 2014) - Abdelali‐Martini, Malika; Dey de Pryck, Jennie
Abstract With major socio‐economic changes in the Middle East and North Africa spurring men's exit from agriculture, women now represent over 60 per cent of the agricultural workforce in several countries. Drawing on original field research, this paper analyses the emergence of female agricultural labour contractors and female wage labour groups in north‐west Syria and compares the outcomes for the contractors' and labourers' empowerment with regard to four dimensions of power or agency: power within, power to, power over and power with. An evolving but delicate balance between continuity and transformation has permitted modest gains in women's empowerment without challenging intrahousehold gender power relations. Copyright © 2014 John Wiley & Sons, Ltd.